A review on some organic acids additives as shelf life extenders of fresh beef cuts - Mohamed, Jamilah; Abbas, Kassim Ali; Abdul Rahman, Russly (Science Publications, 2008)
This study was aiming to present some approaches by which the shelf life of fresh beef cuts was extended. These approaches were based on using organic acids. Therefore the work was started with highlighting the deterioration of some quality attributes due to spoilage and pathogenic microorganisms. These attributes included colour, flavour and lipid oxidation changes. In a given holding temperature, the deterioration are controlled by three major factors, they are pH, water activity and microbial growth. The four organic acids approaches (citric, lactic, acetic and tartaric) were presented as fresh beef shelf life extenders due to their abilities to decrease the pH and antimicrobial effects. The pros and cons of these approaches as well as the latest published researches were stressed at the end of this review. This information helps the researchers and gives them the motivation to develop new superior approach.